How important are foreign shocks in small open economy? The case of Slovakia - Roman Horváth; Marek Rusnák (Charles University in Prague, Institute of Economic Studies (IES), 2008)
In this paper, we provide evidence on the nature and the relative importance of domestic and foreign shocks in Slovak economy based on block-restriction vector autoregression model in 1999-2007. We document well-functioning monetary transmission mechanism in Slovakia. Subject to various sensitivity checks, we find that contractionary monetary policy shock has a temporary negative effect on the degree of economic activity and price level. We find that using output gap instead of GDP alleviates the price puzzle. In general, prices are driven mainly by foreign factors and the European Central Bank monetary policy shock on Slovak prices is more powerful than that of the National Bank of Slovakia. Slovak central bank interest rate policy seems to follow the ECB's interest rates. On the other hand, spectacular Slovak economic growth is primarily driven by domestic factors suggesting the positive role of recently undertaken Slovak economic reforms.
Keywords: E58; F41; F42; 330; small open economy; foreign shocks; monetary policy; Slovakia; euro area; Geldpolitik; Zentralbank; Eurozone; Geldpolitische Transmission; Kleine offene Volkswirtschaft; Slowakei; EU-Staaten